PLEASURE AND PAIN IN THE FORBIDDEN RELATIONSHIPS: A CRITICAL ANALYSIS OF THE GOD OF SMALL THINGS - Swami, Indu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present paper is a sincere attempt to examine how various characters in The God of Small Things suffers as a consequence of breaking the social norms of sexuality, in light of Jeremy Bentham’s pleasure and pain theory which emphasizes that an action is a right action when it creates or its consequence is the greatest happiness of the greatest number. The central character of the novel, Ammu, and her copulation with Velutha is implicitly an attempt to break the artificial social norms of love and sexuality. A critical analysis of the novel reveals that Arundhati Roy, through her protagonists, vividly portrays that acting against social norms is not something easy. However, she highlights, that Ammu and Velutha get punished for breaking ‘the love laws’ does not mean that they deserve it. Roy just shows how the real world works. Pursuing your heart does not guarantee a perfect life because social norms are so deep-rooted in people’s minds that one does not even look if they are good or bad.